ECG changes in birth asphyxia and its correlation with Cardiac troponin-I - Pal, Pankaj; Goel, Manjusha (International Journal of Medical Research and Review, 2015)
Introduction: Cardiac dysfunction is well known in perinatal asphyxia caused by transit myocardial ischemia. Sometimes cardiac dysfunction may be so severe that it can cause congestive cardiac failure and shock that leads to death of newborn. ECG and serum levels of cardiac enzymes can be used to demonstrate impaired myocardial function. Material and Methods: It was a case control study conducted in the department of paediatrics, Gandhi Medical College, Bhopal over a period of 12 months from January 2013 to December 2013. Forty asphyxiated full term neonates were taken as cases and 20 healthy full term neonates as controls. Forty neonates with asphyxia admitted to NICU with gestational age >37 completed weeks and with birth weight >2 kg taken as cases and twenty healthy full term neonates (37 completed wks) unasphyxiated weighing >2 kg at birth with clear liquor and 1 min Apgar score >7. Results: Myocardial dysfunction was present in 90% of the newborns with severe birth asphyxia and 40% of newborns with moderate birth asphyxia. T wave changes were seen in 80% neonates with severe asphyxia and 33% neonates with moderate asphyxia. In present study, cTn I levels in severely asphyxiated neonates were significantly higher than moderately asphyxiated neonates and control group neonates (4.6 ng/ml, range 2.1 – 7.8, and 1.8 ng/ml, range 0.2 – 4.8 ng/ml and 0.6ng/ml, range 0.2-1ng/ml respectively). Conclusion: We found a linear relationship between levels of cardiac troponin-I and birth asphyxia. Therefore cardiac troponin-I level may be useful in predicting the mortality and outcome in perinatal asphyxia.